ReaLSAT, a global dataset of reservoir and lake surface area variations - Ankush Khandelwal; Anuj Karpatne; Praveen Ravirathinam; Rahul Ghosh; Zhihao Wei; Hilary A. Dugan; Paul C. Hanson; Vipin Kumar (Scientific Data, 2022)
Measurement(s) surface area of lakes and reservoirs Technology Type(s) unsupervised machine learning on satellite derived data